2010
DOI: 10.1111/j.1525-1594.2009.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sustained Hemodiafiltration With Continuous Venovenous Hemodiafiltration for the Treatment of Critically Ill Patients With Acute Kidney Injury

Abstract: Despite improvements in medical care, the mortality of critically ill patients with acute kidney injury (AKI) who require renal replacement therapy (RRT) remains high. We describe a new approach, sustained hemodiafiltration, to treat patients who suffered from acute kidney injury and were admitted to intensive care units (ICUs). In our study, 60 critically ill patients with AKI who required RRT were treated with either continuous venovenous hemodiafiltration (CVVHDF) or sustained hemodiafiltration (S-HDF). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 31 publications
(40 reference statements)
2
59
1
Order By: Relevance
“…However, our findings (19) are different from those of Wald et al (4) as well as many of the previous observational studies (1,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Instead, our findings are more consistent with previous RCTs (1,15,16,(30)(31)(32)51,52). It is unclear why our findings diverge from other large retrospective studies and show no increased hazard for nonrecovery from AKI with IHD.…”
Section: Discussionsupporting
confidence: 80%
“…However, our findings (19) are different from those of Wald et al (4) as well as many of the previous observational studies (1,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Instead, our findings are more consistent with previous RCTs (1,15,16,(30)(31)(32)51,52). It is unclear why our findings diverge from other large retrospective studies and show no increased hazard for nonrecovery from AKI with IHD.…”
Section: Discussionsupporting
confidence: 80%
“…RCTs comparing these two modalities have failed to provide evidence for the survival benefits of CRRT over IHD [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. The clinical question "which is the best treatment strategy for critically ill patients with AKI requiring RRT ?…”
Section: Rrt Modality and Rrt Mode In Patients With Akimentioning
confidence: 99%
“…They found no significant difference in mortality between the 2 groups. [6][7][8] However, a recent study reported that EDD might reduce mortality in patients with AKI in comparison to CRRT. 9 Thus, we sought to systematically review the current literature and analyze all studies comparing EDD to CRRT for the treatment of AKI in critical illness.…”
mentioning
confidence: 95%